2008
DOI: 10.11130/jei.2008.23.2.237
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Free Trade Agreements: an Empirical Investigation

Abstract: This paper studies how income inequality affects the probability of signing free trade agreements (FTAs) • JEL classification: F15, F12•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Although most of the FTAs/CUs have long staging periods in internal tariff reduction and some of them may violate the spirit of the Article XXIV, they are offered much less scope for exchanging arbitrary preference than PTAs. This paper is related to Dutt and Mitra (2002) and Liu (2008), who find empirical support for the median voter model (pro-labor) in trade policies and FTA/CU formation respectively. This paper distinguishes partial-scope from full-fledged RTAs and provides a better Service agreements signed under the GATS Article V are not considered separately in this paper because they usually parallel to FTAs/CUs in goods.…”
Section: " ---Gatt Enabling Clause (Italics Added By Author)mentioning
confidence: 86%
“…Although most of the FTAs/CUs have long staging periods in internal tariff reduction and some of them may violate the spirit of the Article XXIV, they are offered much less scope for exchanging arbitrary preference than PTAs. This paper is related to Dutt and Mitra (2002) and Liu (2008), who find empirical support for the median voter model (pro-labor) in trade policies and FTA/CU formation respectively. This paper distinguishes partial-scope from full-fledged RTAs and provides a better Service agreements signed under the GATS Article V are not considered separately in this paper because they usually parallel to FTAs/CUs in goods.…”
Section: " ---Gatt Enabling Clause (Italics Added By Author)mentioning
confidence: 86%
“…An increase in inequality reduces the desirability of signing an RTA, ceteris paribus, if a country is more labor abundant relative to its partners. 5 Based on Levy (1997) and Liu (2007), Liu (2008) derives the same pro-labor prediction of the median voter model in the case of free trade agreements. 6 Please note that this model is a modified specific-factor model rather than a Heckscher-Ohlin model.…”
Section: Theoretical Predictionsmentioning
confidence: 90%
“…This article is related to the work of Dutt and Mitra (2002) and Liu (2008), who find empirical support for the median voter model (pro-labor) in trade policies and FTA/CU formation, respectively. This article distinguishes partial-scope from full-fledged RTAs and provides a better understanding of the conflicting distributional forces behind RTA formation.…”
Section: Introductionmentioning
confidence: 96%
“…The value ranges from 20 (for a pair of completely autocratic states) to 20 (for a pair of fully democratic states). Numerous studies have shown that a pair of democracies is more likely to enter PTAs because democratic leaders utilize PTAs to increase public support for their political tenures (Drury, Krieckhaus & Yamamoto, 2014;Liu, 2008;Mansfield et al, 2002;Yamamoto Rosenbaum & Krieckhaus, 2016). At the same time, several studies suggest that highly democratic countries are prone to choose bilateral PTAs over multilateral PTAs, as bilateral PTAs can bring deals more customized to benefit member states and, therefore, find it easier to pass a long ratification process at home (Levy, 1997;Mansfield & Milner, 2012;Molders, 2012).…”
Section: Methodsmentioning
confidence: 99%